Bacteria Effect on Health and Human-Review (American International Journal of Biology and Life Sciences, 2019)
Microbes are an important component of the microbiology  eco-system in the human gut, which is colonized by 1014 bacteria , ten times more than the human cells. Gut bacteria take  an important role in human health, like  supplying essential nutrients, synthesizing vit. K, aiding in the digestion of cellulose, and promoting angiogenesis and enteric nerve function. However, they can also be potentially harmful due to the change of their composition when the gut ecosystem undergoes abnormal changes in the light of the use of antibiotics, illness, stress, aging, bad dietary habits, and lifestyle. Dysbiosis of the gut bacteria communities can cause many chronic diseases, such as inflammatory bowel disease, obesity, cancer, and autism.